Ramp Generator has Separate Slope and Frequency Controls - Malvar, Henrique S. (Electronics, 1979)
Isolating with four analog switches the frequency-determining portion of the circuit from that controlling the charging and discharging of its RC integrator, this ramp generator achieves independent selection of slope ratio and repetition rate. Such a unit is useful in a music synthesizer, where timbre must be changed without affecting a note's fundamental frequency.